(untitled) (Medicine Today, 2013)
To determine the relation between iron deficiency and the status of thyroid hormones in iron deficient patients. This case control study was done in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU), during July 2006 to the June, 2007. Iron deficiency patient was considered as case a healthy control subject was considered as control. A total of 80 subjects were selected for study from those who were attended in out patient department of the above mentioned hospital were enrolled in this study. The mean (±SD) age of case and control were 33.48±11.03 years and 35.40±12.30 years with the range of 16-60 years and 15-60 years respectively. Male female ratio was 1:1.6 in the whole study subjects. Hemoglobin concentration, serum ferritin concentration were significantly (p<0.05) higher in control group but serum TSH level was significantly (p<0.05) higher in case group, however, serum FT3 was almost similar between case and control groups. In iron deficient patients, serum ferritin had no significant negative correlation (r=-0212; p>0.05) with serum TSH and no correlation with serum FT4 concentrations and serum FT3 concentration which were (r=0.055; p>0.05) and (r=0.147; p>0.05) respectively. In control subjects, serum ferritin revealed that there was significant negative correlation (r=-0.337; p<0.05) serum TSH. However, serum ferritin with serum FT4 concentration and serum ferritin with serum FT3 level showed no statistically significant correlation which were (r=0.283; p>0.05) and (r=0.145; p>0.05) respectively. On the other hand, there were no significant (p>0.05) correlation of hemoglobin concentration and serum ferritin with serum TSH, free T3 and free T4 concentrations both in case and control group. There were no significant (p>0.05) difference among serum TSH, free T3 and free T4 concentrations between male and female in both groups. Serum TSH level was significantly (p<0.05) higher in iron deficient patients and no significant negative correlation, serum ferritin level. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.13941 Medicine TODAY Vol.24(1) 2012 pp.1-4